The Rise of Populism in Spain. An Analysis of Hegemonic Struggles and Shifts in Power Relations - Schafgans Muñoz, Johanna (Política. Revista de Ciencia Política, 2022)
In this paper I develop an explanatory approach to the specific social conditions of alternative variants of populism in Spain, focusing on how the hegemonic positions of different political actors have developed in Spain since the crisis-related reorganization processes. To approach these issues, I’m conducting a qualitative media and document analysis and expert interviews. Initial findings indicate that the euro crisis and the protest movements around the 15-M seem to have acted as a destitute moment in which the previous social and hegemonic order was called into question. The Spanish government reacted to this political uprising with more repression. This situation enabled new actors to enter the political arena and made new forms of politics (populism) necessary to achieve hegemony.